Variability of gluten intolerance in treated childhood coeliac disease. Issue 2 (February 1979) - McNicholl, B; Egan-Mitchell, B; Fottrell, P F
Abstract : Fifty children consecutively attending a clinic for coeliac disease co-operated in a trial; 10 found to have flat mucosa were excluded. Forty children of mean age 9.8 years, whose duodenal or jejunal mucosa had returned to normal or near normal appearance after a mean of 5.8 years on gluten-free diets, were put back on normal diets. In 37, mucosal occurred in a mean of 16.9 months (four to 74 months). Four of the 37 had serial biopsies, in which mucosal enzymes (particularly lactase) fell and interepithelial lymphocyte counts rose before the mucosal morphology was regarded as definitely 'coeliac'. Three children had normal mucosal appearance after 58 to 73 months on normal diets, one of whom showed temporary mucosal abnormalities, another having occasionally low enzymes, in both suggesting underlying gluten sensitivity. Lactase suppression and raised IEL counts appear to be sensitive indicators of gluten intolerance. In our experience, a diagnosis of coeliac disease based on severe mucosal damage and a satisfactory response to a gluten-free but milk-containing diet implies a very strong likelihood of permanent or prolonged gluten intolerance, but with a striking variability in its expression.